Quark Mass, Quark Compositeness, and Solution to the Proton Spin Puzzle - de Souza, Mário Everaldo (Scientia Plena, 2011)
This work shows that the proton spin puzzle and the origin of quark mass are natural consequences of the compositeness of quarks which also generates a continuous symmetry breaking. And is also quark compositeness what is behind the Kobaiashi-Maskawa matrix. Moreover, the paper shows that prequarks (primons) have already been found by the first EMC experiment in the 1980s.